Neuropsychiatric symptoms in the prodromal stages of dementia - Stella, Florindo [UNESP]; Radanovic, Marcia; Balthazar, Marcio L. F.; Canineu, Paulo R.; Souza, Leonardo C. de; Forlenza, Orestes V. (Lippincott Williams & Wilkins, 2014)
Purpose of reviewTo critically discuss the neuropsychiatric symptoms in the prodromal stages of dementia in order to improve the early clinical diagnosis of cognitive and functional deterioration.Recent findingsCurrent criteria for cognitive syndrome, including Alzheimer's disease, comprise the neuropsychiatric symptoms in addition to cognitive and functional decline. Although there is growing evidence that neuropsychiatric symptoms may precede the prodromal stages of dementia, these manifestations have received less attention than traditional clinical hallmarks such as cognitive and functional deterioration. Depression, anxiety, apathy, irritability, agitation, sleep disorders, among other symptoms, have been hypothesized to represent a prodromal stage of dementia or, at least, they increase the risk for conversion from minor neurocognitive disorder to major neurocognitive disorder. Longitudinal investigations have provided increased evidence of progression to dementia in individuals with minor neurocognitive disorder when neuropsychiatric symptoms also were present.SummaryAlthough neuropsychiatric symptoms are strongly associated with a higher risk of cognitive and functional deterioration, frequently the clinician does not acknowledge these conditions as increasing the risk of dementia. When the clinician accurately diagnoses neuropsychiatric symptoms in the prodromal stage of dementia, he could early establish appropriate treatment and, may be, delay the beginning of clinical and functional deterioration.
Keywords: Alzheimer's disease; mild behavior impairment; minor neurocognitive disorder; neuropsychiatric symptoms; prodromal dementia